А. P. Chekhov’ Reception in Russian “Women’s Prose” of the End of 20th - the Beginning of 21st Century - S. Zhang (Научный диалог)
The problem of literary traditions continuity, namely the influence of the literary heritage of A. P. Chekhov on contemporary Russian women’s prose is examined. The women’s prose in this article is considered as a literary and social phenomenon, which has some peculiarities in the artistic depiction of reality. In particular, women’s prose is characterized by accentuation on spiritual qualities of character, his / her inner world, feelings, inner struggle. It is noted that in the constant treatment of women writers to A. P. Chekhov’s works the author of the article sees gender base: contemporary writers are close to the topic of the origin of the feelings against the background of everyday hustle and bustle in his works, misunderstanding of the characters and, as a consequence, their loneliness. In addition, women writers often turn to books with memorable female characters, having typical features. Material for the study were the works by the famous contemporary Russian women writers: L. Ulitskaya, L. Petrushevskaya, T. Tolstaya, V. Tokareva, D. Rubina. The author concludes that the obvious intertextual links with the Chekhov’s pretext can be traced in their works, shows the influence of Chekhov’s ideas on the works of representatives of Russian women’s prose of the present time, and at the same time notes that women writers originally interpret the eternal themes of love and loneliness.